2011
DOI: 10.5771/0935-9915-2011-2-107
|View full text |Cite
|
Sign up to set email alerts
|

Introduction: New Perspectives on the Quality of Working Life

Abstract: Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden. Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen. Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in der dort genannten Lizenz … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…A considerable body of empirical studies has found that job quality affects wellbeing and happiness. Low-quality employment has been associated with lower levels of self-reported life satisfaction and happiness, compared to those of people with higher quality jobs (Gallie 2013a;Sánchez-Sánchez and McGuinness 2013;Keller et al 2014), and this association holds true across different institutional settings Kattenbach and O'Reilly 2011). Although those in poor-quality jobs have lower levels of life satisfaction, they are often more satisfied than people who remain unemployed (Grün, Hauser, and Rhein 2010).…”
Section: Job Qualitymentioning
confidence: 99%
“…A considerable body of empirical studies has found that job quality affects wellbeing and happiness. Low-quality employment has been associated with lower levels of self-reported life satisfaction and happiness, compared to those of people with higher quality jobs (Gallie 2013a;Sánchez-Sánchez and McGuinness 2013;Keller et al 2014), and this association holds true across different institutional settings Kattenbach and O'Reilly 2011). Although those in poor-quality jobs have lower levels of life satisfaction, they are often more satisfied than people who remain unemployed (Grün, Hauser, and Rhein 2010).…”
Section: Job Qualitymentioning
confidence: 99%
“…A considerable number of empirical studies have found that job quality affects wellbeing and happiness. Being in a 'low-quality job' is associated with lower levels of self-reported life satisfaction and happiness than being in a 'high-quality job' 4 ; this is an association that holds true across different institutional settings (Gallie, 2013a;Kattenbach and O'Reilly, 2011). Although those in low-quality jobs seem to enjoy lower-than-average levels of life satisfaction, these levels are often still higher than those experienced by people who remain unemployed (Grün et al, 2010).…”
Section: Job Qualitymentioning
confidence: 99%
“…A considerable body of empirical studies has found that job quality affects wellbeing and happiness. Low-quality employment has been associated with lower levels of self-reported life satisfaction and happiness, compared to those of people with higher quality jobs (Gallie 2013a;Sánchez-Sánchez and McGuinness 2013;Green et al 2014;Keller et al 2014), and this association holds true across different institutional settings (Gallie 2007;Kattenbach and O'Reilly 2011). Although those in poor-quality jobs have lower levels of life satisfaction, they are often more satisfied than people who remain unemployed (Grün, Hauser, and Rhein 2010).…”
Section: Job Qualitymentioning
confidence: 99%